AB0970 Ultrasonography in Diagnosis and Management of Iliolumbar Syndrome: Case Series. (15th July 2016) - El Khoury, N.; Zebouni, S.H.; Revel, M.; Fayad, F.
Abstract : Background: The iliolumbar ligament may be an important cause of acute and chronic Low Back Pain (LBP). The diagnosis of iliolumbar ligament inflammation is based on clinical history and physical examination which lack sufficient specificity. The treatment consisted of the standard care used in common LBP. Nowadays, ultrasonography (US) is used in routine practice in rheumatology for diagnostic purposes and to guide local injections but this technique is generally confined to assess peripheral joints and peri-articular structures. Objectives: To describe the role of ultrasonography in the diagnosis and treatment of LBP related to an inflammation of the iliolumbar ligament. Methods: From December 2012 till December 2015, all patients with clinically suspected iliolumbar syndrome were included in this study. Patients underwent an ultrasonography to confirm the diagnosis. For this technique, the patient is in the prone position and the probe is positioned almost horizontally for L5 and in slightly oblique direction for L4. To confirm the diagnosis, we should have a swollen hypoechoic iliolumbar ligament with reproduction of the usual back pain during the passage of the probe above the ligament 1 . Also, the thickness of the inflamed ligament should be higher than 1mm. The US was always performed bilaterally so we can compare both sides. Patients who failed standard treatment were injected under US-guidance or in clinic with 80mg of methyl-Prednisolone and 5cc of local xylocaïne. The patient's assessment of usual LBP was recorded 20mn after the injection of xylocaïne. Results: 30 consecutive patients with clinically suspected iliolumbar syndrome (LBP with presence of tenderness on palpation of the posterior/ medial aspect of the iliac crest) were evaluated by US. Patients included in this study were relatively young with a mean age 38.87 years (22–65 years). The sex ratio is 5/1 (female/male). As suspected, X-ray and/or MRI of the lumbar spine and pelvis, when performed, were normal in most cases. Few cases of mild degenerative disc disease are noted. US showed, in all patients, an inflammation of the iliolumbar ligament (fig.1 ). In four patients, the iliolumbar ligament was inflamed at both sides. The mean thickness of the ligament was 2.64 mm (1.5–6mm). There was an associated tendonitis of the gluteus medius muscle in 5 patients, diagnosed also on US. The patients received a treatment with NSAIDs and a 12-session course of physical therapy, but this standard therapy was insufficient in 67% of cases. Twenty one (70%) patients received injection of 80 mg of methyl-Prednisolone and 5cc of local xylocaïne, 11 patients under US-guidance and 10 in clinic. All patients noted the disappearance of the usual LBP 20mn after the injection (effect of local anesthesia). Conclusions: Ultrasonography allows the diagnosis of iliolumbar syndrome in patients with LBP. It is a useful tool to guide infiltrations of corticoids as an effective therapy for this pathology. Prospective randomized trials are needed to confirm our conclusions. References: Christelle Darrieutort-Lafitte, Olivier Hamel, Joelle Glemarec, Yves Maugras, Benoit Le Goff. Ultrasonography of the lumbar spine: Sonoanatomy and practical applications. Joint Bone Spine 81 (2014) 130–136. Acknowledgement: None declared Disclosure of Interest: None declared